2021
DOI: 10.1186/s12974-021-02154-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aberrant innate and adaptive immunity based on changes in global gene expression in the blood of adults with autism spectrum disorder

Abstract: Background Autism spectrum disorder (ASD) is characterized as a neurodevelopmental disorder, and one of the main hypotheses regarding its cause is genetic factors. A previous meta-analysis of seven microarray studies and one RNA sequencing (RNA-seq) study using the blood of children with ASD identified dysregulation of gene expressions relevant to the immune system. In this study, we explored changes in global gene expression as the phenotype of ASD in the blood of adults with ASD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
5
10
0
2
Order By: Relevance
“…The upregulated expression levels of both BATF2 and FCGR1A in our Israeli cohort of whole blood samples from children with ASD (Fig. 1) corroborate ndings from a recent Japanese RNA-seq study in whole blood from adults with ASD 17 . To our knowledge our study provides the rst validation of a genome-wide RNA-seq study with ASD blood samples.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The upregulated expression levels of both BATF2 and FCGR1A in our Israeli cohort of whole blood samples from children with ASD (Fig. 1) corroborate ndings from a recent Japanese RNA-seq study in whole blood from adults with ASD 17 . To our knowledge our study provides the rst validation of a genome-wide RNA-seq study with ASD blood samples.…”
Section: Discussionsupporting
confidence: 88%
“…A recent RNA-seq study of whole blood from adults with ASD found dysregulated transcription of genes implicated in innate and adaptive immunity. These included upregulated expression of BATF2 and FCGR1A 17 , as con rmed in our current study of whole blood from children with ASD. The consequences to the immune system, of dysregulation in children with ASD of the four genes observed in our study (Fig.…”
Section: Dysregulated Asd Genes and Immunitysupporting
confidence: 77%
See 2 more Smart Citations
“…Patients with these brain diseases share deficits in cognition, blunted mood, restricted sociability and abnormal behavior to various degrees. Transcriptome studies have identified expression alterations of immune-related genes (IRGs) in postmortem brains of AD( 7 ), PD( 8 ), ASD( 9 ), SCZ( 10-14 ) and BD( 10 ) separately. Cross-disorder transcriptomic studies further highlighted changes in IRGs( 15, 16 ).…”
Section: Introductionmentioning
confidence: 99%